The generation of Pan-Slavism and Russian Slavophiles - Timura, Viktor (Napredak, 2026)
The issue of cooperation between Slavic peoples remains relevant to this day. Its beginnings reach way into the past, at the very least to the period of the Great Moravian state. A certain peak happened in the 19th century, particularly in connection with the revolutionary years of 1848-1849, when a wave of revolution swept across European nations, especially the Slavic peoples who endured oppression within Austrian-Hun garian Monarchy. In this process, it is noteworthy that the impulse for mutuality and cooperation among the Slavic peoples originated in Slovakia and subsequently spread to all Slavic nations. It served as a stimulus for Slavophilia in Russia as well, from where individuals came to Slovak and Czech representatives not only to gain experience, but also to admire them for their Slavic enthusiasm.
Keywords: reciprocity; Slavic; Slavophiles; Russian Slavophiles; Slovak Štúrovci; generations; Pan-Slavism; Czechoslovak society; Slavic Congress; national revival; Russia; messianism; Pan-Germanism